Food Defense – from the concept to current demands of international market (Research, Society and Development, 2021)
The food defense concept emerged in the US in response to the terrorist attacks of September 11, 2001. Thus, the Food and Drug Administration (FDA) and other agencies developed measures to protect the country's food chain from malicious attacks. The objective was to adopt preventive measures against the intentional contamination of water and food, where individuals resort to agents (biological, chemical, or physical) to harm organizations, governments or the population. The vulnerability of the food chain enabled the dissemination of this concept through certifiable standards such as: International Featured Standards (IFS), British Retail Consortium (BRC) and Food Safety Systems Certification (FSSC 22000). This study aims at the emergence of the food defense concept, along with the already known terms: food quality, food safety, food security and food fraud, through regulations, laws, methodologies, and tools for implementing food defense in food production and distribution chains from exporting companies to family businesses. Methodology: qualitative analysis through bibliographic research in Scopus, Web of Science and SciELO databases. Conclusion: it is expected that the results of this study arouse the need for training professionals in the food area, including concepts such as food defense, and that guide the adoption of measures in the conceptual and practical spheres that prevent and control the intentional contamination of food, from to meet the constant demands of the consumer markets and the adoption of norms and legislation in force regarding the quality and safety of food.